Protocol to improve the quality in the formulation of problems in mathematics: A two-dimensional didactic proposal - González Mallo, Ciro; Rivas Rivas, María Clara; Schwerter Cárcamo, Patricia; Bustos Yáñez, Javier; García Hormazábal, Ricardo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyzes the implications of the relationship between reading comprehension and problem solving in mathematics through a detailed analysis of the linguistic formulation of mathematical problems and their resolution in a teaching support manual prepared for this purpose. In this way, different statements of problems in mathematics are detailed to analyze from their verbal structure -according to a growing and integrated complexity- in order to expose their impact on the possibilities of resolution by first-year university students in the Faculty of Engineering from UC Temuco.